Analisis Kewenangan dan Putusan Mahkamah Konstitusi dalam Amandemen Ketiga Undang-undang Dasar 1945 dalam Perspektif Siyasah - Yesi Imelda; Sandy Wijaya (Medina-te : Jurnal Studi Islam, 2021)
The purpose of this paper is to analyze the authority of the Constitutional Court in the third amendment of the 1945 Constitution. This type of writing is by examining library research or secondary data strengthened in primary data that examines the third Amendment of the 1945 Constitution which focuses on on the Authority and Decision of the Constitutional Court. The approach chosen in this study uses a normative juridical approach, which is carried out by examining library materials or secondary data related to the Constitutional Court. the decision is final, this article is very clearly contrary to human rights, with the determination of the nature of the decision of the Constitutional Court because there is no more opportunity for litigants to take legal action.